Evaluation of a Rapid Antigen Test for the Diagnosis of SARS-CoV-2 during the COVID-19 Pandemic - Chih-Chien Cheng MD, PhD; Chia-Chen Liu MD; Ting-Fang Chiu MD; Saint Shiou-Sheng Chen MD (SAGE Publishing, 2022)
Objectives: Reverse transcriptase-polymerase chain reaction (RT-PCR), the reference laboratory method of confirmed SARS-CoV-2 diagnosis, though requiring equipment, is time-consuming. There is a crucial demand for rapid techniques such as antigen detection test during the pandemic. This study assessed whether a rapid antigen detection (RAD) test was an effective and essential method for the early diagnosis of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) during the COVID-19 pandemic. The probability of public screening at home and the application of RAD during the novel SARS-CoV-2 outbreak were also topics of interest. Methods: A retrospective analysis based on the systemic screening for COVID-19 was conducted at Taipei City Hospital (TCH) from May 28 to June 06, 2021, the first week of outbreak in Taiwan. The results of the RAD and RT-PCR tests were collected from 5 major branches of the TCH. Results: We collected a total number of 6368 cases. We found that the sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and accuracy ranged from 60.5% to 78.6% (mean 66.0%), 98.2% to 99.9% (mean 99.0%), 74.4% to 97.8% (mean 82.8%), 94.0% to 98.4% (mean 97.5%), and 93.8% to 98.3% (mean 94.2%), respectively. Although the sensitivity score was not high (up to 95% or higher), the other results were satisfactory, with an accuracy of more than 93% in all branches. Furthermore, it had high specificity, PPV, NPV, and accuracy. Conclusion:We concluded that RAD could be a quick and feasible method to identify individuals infected with SARS-CoV-2 from non-contagious individuals during the COVID-19 outbreak. A RAD test was an effective and essential method for the early diagnosis of SARS-CoV-2 during the COVID-19 pandemic.